EUPHEMISMS IN PHILIPINE CULTURE POTRAYED IN FILIPINO MOVIES - Ramon B, Jay; Lauder R, Arroyo; Juelyn P. Romero, Atienza (SIGEH ELT : Journal of Literature and Linguistics, 2023)
This study explores the euphemisms in Philippine culture portrayed in Filipino movies. This study attempts to answer the research questions: (1) What euphemisms are used in the movies (a) Remington and the Curse of Zombadings and (b) Die Beautiful along with metaphor, idioms, and hyperbole? and (2) What are the functions of the euphemisms used in the two movies? The researchers analyzed the data using the lens of latent content analysis and qualitative analysis to unpack the meanings and relationships. The data were taken from the script supported by the transcription method. The method of data analysis is described in great detail–Transcribing, Data Reduction, and Data Selection. Study found various euphemisms under metaphor (ng ganun, confimed, Diana Rose, in fairness, magbooking, kaligayahan, and usapan ng mga tao ‘to); Idioms (malakandila ang mga daliri, natuluan ng kandila); Hyperbole (dynamite, mitsa, busy po masyado, hindi kailangan ng utak dito) in the movie Remington and the Curse of Zombadings. In the movie Die Beautiful, numerous euphemisms were also categorized on its types: Metaphor (pambabae, pag inampon mo yang batang yan magiging babae ka na, bantot, lason, mani, wala naman sa kalingkingan, hindi ka pa nagpapabreastfeeding, magkapechay, number 2; Idioms (pakainin kita ng sangkatutak na star margarine, nanginginig yung matres, naputikan ka na); Hyperbole (kahit anino, wala, anak lang ng anak hindi naman nanay, anglalaking wawasak sa’aking puri, 3 inches lang yung ano). Therewere variations of functions seen according to the speaker euphemisms' contexts and purpose, made to inform (conveys new information), evaluate (conveys opinions and attitude), modalize (conveys attitude towards truth and utterance), convince(persuade), criticize (for giving criticisms), order (giving instructions), and refuse (to deny or reject).